Upcoming Therapeutic Modalities for the Treatment of Keloids: An Update - Uma Keyal; Anil Kumar Bhatta (Nepal Journal of Dermatology, Venereology & Leprology)
Introduction: Keloids are benign dermal tumors that generally form by local fibroblast proliferation and excessive collagen production following skin trauma. Several methods have been described for the treatment of keloid, often with suboptimal results and recurrences.